The effects of traumatic brain injury on complex figure test performance : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Bowie, Jonathan M. H (Massey University, 1997)
Patients with Traumatic Brain Injury (TBI) have performed below norms on the Complex Figure Test (CFT) and this has been attributed to lack of organization (Binder, 1982). The present study compared 105 TBI subjects with 59 Controls in terms of accuracy and organization to examine whether lower TBI subject organization was associated with subsequent lower accuracy. Results showed that TBI subjects scored lower accuracy than controls on copy, recall and delay trials but did not score lower for organization (as measured by Hamby, Wilkins & Barry, 1993). Both groups were consistent in organizational approach across the three CFT trials, and copy organization scores of both groups were positively correlated with accuracy scores on recall and delay trials. This suggests that TBI subjects do have a problem with the CFT, but it cannot be linked to copy organization on the basis of evidence from the present study. The unexpected results were attributed to methodological problems involving the population samples and the organization measure.
Keywords: Brain; Wounds and injuries